MENTAL HEALTH, DRUGS AND REUPDATING PROHIBITIONISM IN THE BOLSONARO GOVERNMENT - Albuquerque, Cynthia Studart; Gonçalves, André de Menezes; Lima, Leandro Sobral de; Cruz, Liziane Silva (Argumentum, 2023)
The article critically discusses the advance of conservatism in the context of mental health and drug policy actions in the country, a process that has contributed to a re-updating of prohibitionism, particularly in the Bolsonaro government. From the civil-military dictatorship to the recent far-right administration, legislation and regulations on drugs have advanced and strengthened in terms of punishment, control and criminalization of those considered undesirable. Even so, struggles and resistance are forged in the scope of protection and care in the themes of drugs and mental health, as indicated by the bibliographical and documental research present in the text based on a historical-critical analysis. The horizon signals countless challenges, as well as possibilities for the realization of social and human rights for people with relationships with the so-called drugs.